Plan-based Translation Assessment An Alternative to the Standard-based cut-the-feet-to-fit-the-shoes Style of Assessment - Zhong, Yong (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe practice of translation/interpreting is guided by a diversity of theories and so is the instruction of translation/interpreting, though arguably to a lesser extent. Yet, pedagogical assessment of translation, especially in relation to the assessment of translation works by students, mostly seem to fall into one kind, one which is overwhelmingly based on an imagined standard and concerned with accurate and adequate comformity to the standard.The author of this paper, while experimenting with game theory and problem-based learning in the teaching of translation and interpreting, has been rethinking the assessment process. As a result, he has developed what he sees as an alternative system of marking, one which he calls planbased assessment and which aims to mark a student’s work/performance against the specific plans formulated by the individual student in conjunction with the instructor rather than against the imagined singular homogeneous standard imposed by an authority. He believes that this system is more conducive than the conventional standard-based assessment to the teaching of translation/interpreting in liberal arts education as it facilitates the development of subjectivity, vision, different learning styles, creative/critical thinking power, and problem-identifying and -solving skills.In this paper, he will discuss the characteristics of plan-based assessment system in comparison to those presumably comprising the conventional system. Comparison will also be made to the sort of assessment advocated by functional theories of translation as they inspired and informed the construction of plan-based assessment. The paper will conclude with a case study of the use of plan-based assessment.